Influence of different types of margins in the fish assemblage from an urban river - Thais Aparecida Soinski; Lucio Antônio Stefani Pinheiro; Daiane Elen Cavallari; Marta Severino Stefani; Welber Senteio Smith (Boletim do Instituto de Pesca)
The presence or absence of a fish species may be associated with the physical and chemical characteristics of the water, in addition to the state of preservation of the riparian zone. This study examined whether the taxonomic fish composition in an urban river varies along three riparian zone preservation conditions: preserved, intermediate preservation and degraded. Six urban stretches of the Sorocaba/São Paulo River were selected for this study, with monthly sampling being carried out from June 2019 to February 2020. The samplings were carried out with the aid of a sieve, dip net, and trawl. Regarding the types of margins and environmental variables, the Principal Component Analysis explained 97.49% of the data variation, axis 1, which explained 91.85% of the total variation, was formed by the variables conductivity and total dissolved solids. Axis 2, which explained 5.64% of the variation, was formed by Sun Rays% and Siltation%, being inversely proportional to Riparian Forest%. For the ichthyofauna, the samples consisted in 50,983 fish distributed in 5 orders, 8 families, and 12 species. Cyprinodontiformes had the highest abundance, with 96.96% of the total number of individuals, followed by Siluriformes (2.39%), and the sum of the other orders did not reach 1% of the total collected. According to each type of margin, it was possible to register 11,592 individuals for the Margin A í  preserved, with S=8 species, being 2 exclusive (Corydoras flaveolus and Hoplosternum littorale) and 3 exotic (Coptodon rendalli, Pterygoplichthys ambrosettii, and Poecilia reticulata), the latter was dominant in all types of margins. For Margin B í  intermediate preservation, 19,645 individuals were sampled, with S=5 species, no exclusive species, only exotic and more tolerant native species such as Hoplias malabaricus and Hypostomus ancistroides. For Margin C í  degraded, 19,746 individuals were recorded, the largest number of species (S=10), 3 were exclusive to this type of margin (Psalidodon fasciatus, Rhamdia Quelen, and Geophagus brasiliensis). The pairwise comparison (similarity percentage) showed that the assemblage structure was different for the types of margins. The Canonical Correspondence Analysis explained 92.46% of the total data variation, showing the relationship of species to environmental data. It is evident the importance of preservation of micro-habitats still present in the locals sampled, since different anthropic pressures cause great loss of diversity, especially for native and more sensitive species.